Age effects on retinal blood flow assessed using spectral-domain optical coherence tomography doppler - Yusof, Firdaus; Tayyari, Faryan; Flanagan, John G; Hudson, Christopher (Association for Research in Vision and Ophthalmology, 2012)
Purpose: : To determine the impact of healthy aging upon total retinal blood flow as derived by Spectral-Domain, Optical Coherence Tomography Doppler SD-OCT.